THE EFFECT OF COOPERATIVE LEARNING TEAM ASSISTED INDIVIDUALIZATION WITH SAVI APPROACH TO THE STUDENTS’ MATHEMATICS ACHIEVEMENT VIEWED FROM THEIR LEARNING STYLE - Putri Sintia Gusantika; Mardiyana Mardiyana; Ikrar Pramudya (Proceedings Education and Language International Conference, 2017)
This research aims to determine the effect of teaching strategy to learning approach, mathematics learning style and the interaction between them to the students’ mathematics achievement. This research design was a quasi-experimental research with a 2x3 factorial design. The population of this research is all students of eleventh grade students of private vocational school in Grobogan academic year 2016/2017. Sampling was done by stratified cluster random sampling. Data were analyzed using two-way analysis of variance with different cells. Based on the research results, it was obtained that: (1) the students’ mathematics achievement who were taught by TAI learning model with SAVI approach better than direct instructional model, (2) the mathematics achievement of students with auditory learning styles were better than those with visual and kinesthetic learning style, whereas mathematics achievement of students with visual learning style were similar to those with kinesthetic. (3) in the visual and auditory learning styles, the students who were taught by using TAI with SAVI and direct instructional model had the same mathematical achievements, meanwhile for the students with kinesthetic learning style who were taught by using TAI with SAVI had better achievement than those who were taught by direct instructional model. (4) on TAI model with SAVI, students with all kinds of learning style had the similar mathematical achievement, while in direct instructional model, students with auditory learning style had better achievement than those with kinesthetic learning style. At each teaching strategy, the students with visual, auditorial or kinesthetic learning style had the same mathematical achievement. Keywords: TAI SAVI, VAK Learning Style, Mathematics Achievement